Automatic semifluid mass dispenser - Samborski, Tomasz; Zbrowski, Andrzej; Kozioł, Stanisław; Mrozek, Mirosław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
The article presents an innovative method for hair dye dispensing and a prototype device enabling automatic dispensing of hair dyes and other semifluid substances. The dispenser makes it possible to programme colour compositions and to precisely dispense the programmed amounts of dyes from three different tubes to combine colours and achieve the desired, known or new, colour and tonal value, as requested by the client. With the dispenser’s software, the hairdresser can create interlinked databases of applications and mixtures and ensure rational management of the substances used. The modern design, compact structure, and automated operation decide on the innovativeness of the dispenser. The article discusses the genesis of the project, the functional and technical assumptions of the innovative device, as well as the design and development of the prototype and performance of functional tests, paying particular attention to the presentation and description of the following: (1) the original structural solutions; (2) the operation of functional modules that are responsible for positioning and identifying dye tubes, dispensing dyes in precisely defined amounts, monitoring the composition of the colour formula, and ensuring optimum dye use; and (3) the user interface. The structure of the device was developed by joining metal structural elements produced with the use of technologies typical for machine construction with commercial components (drives and controllers) and components produced with the use of additive manufacturing technologies responsible for the complete integration and design of the device. The original structural solution of the device is protected by intellectual property rights under patent applications. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)